The Scholarly Movement In Linguistic And Literary Studies In The City Of Nablus A Historical And Analytical Study/ الحركة العلمية في العلوم اللسانية والأدبية في مدينة نابلس دراسة تاريخية تحليلية - Saadiya Hamadi Mizal; Othman Abdulaziz Saleh (Ijaz Arabi Journal of Arabic Learning, 2026)
This study addresses the scholarly movement in linguistic and literary sciences in the city of Nablus, one of the prominent intellectual centers in the Levant during the Islamic era, due to its significant contributions to the Arabic language and its various sciences. The research highlights the city’s attention to Arabic linguistic studies, particularly in grammar, morphology, and language, and their role in supporting religious sciences, alongside the flourishing of literary activity in both poetry and prose. The study also examines the contributions of Nablus scholars in advancing linguistic and literary studies, introducing the most prominent linguists, grammarians, poets, preachers, and writers who played a key role in establishing the city’s scholarly status, whether through teaching, authoring, or engaging in cultural life in major centers such as Damascus, Baghdad, and Cairo. Furthermore, the research emphasizes the pivotal role of these scholars in enriching non-Arabic-speaking communities through their educational and cultural journeys, spreading Arabic language and knowledge beyond the Arab world. The study employs a historical-analytical approach to trace the emergence and development of this scholarly movement, analyzing literary and linguistic texts from historical sources. It concludes that Nablus formed a fertile intellectual environment that preserved and promoted the Arabic language, and its scholars actively contributed to enriching Arabic linguistic and literary heritage and disseminating it among diverse peoples, reflecting the city’s significant cultural and civilizational status in Islamic history.